Relationship between asymmetry of transverse sinus and difference in intraocular pressure Based on MRV imaging examination - Dan Zhu; Weiguang Zhang; Dongtai Zhang; Dong Qiu; Zhenyang Yu; Yiwen Jiang (SLAS Technology)
Transverse sinus asymmetry refers to the inconsistencies in the shape structure, size or blood flow of the intracranial transverse sinus. Intraocular pressure difference refers to the obvious difference in intraocular pressure between the two eyes. Transversal sinus asymmetry may be correlated with intraocular pressure difference, but the mechanism of correlation is still unclear. To investigate the relationship between transverse sinus asymmetry and IOP differences based on MRV examination, and to explore the possible mechanism. Patients with transverse sinus asymmetry were selected and examined using the MRV technique. At the same time, the patients' IOP was measured using standard methods of IOP measurement. Correlation analysis and statistical methods were used to evaluate the association between transverse sinus asymmetry and IOP differences. There was a statistically significant distinction observed between groups I and V (Z = 6.78, P < 0.01). Significant variations were also noted in the intraocular pressures across all groups, encompassing the average measurements of the right eye and left eye, along with the variance between the two (right eye: F = 15.43, P < 0.01; left eye: F = 4.62, P = 0.002; variance between eyes: F = 41.79, P < 0.01). The asymmetry of the transverse sinus exhibited a negative relationship with the intraocular pressure of the right eye (r = 0.51, P < 0.01) and the difference between the pressures of the two eyes (r = 0.79, P < 0.01); no significant association was found between the asymmetry and the left eye's intraocular pressure. In conclusion, a certain correlation exists between the intraocular pressures of the left and right eyes and the morphology of the transverse sinus. When the transverse sinus is thicker on one side, the corresponding drainage veins are thicker, resulting in lower intraocular pressure on that same side.